The murine endogenous retrovirus MIA14 encodes an active aspartic proteinase that is functionally similar to proteinases from D-type retroviruses - Strísovský, Kvido; Smrz, Daniel; Fehrmann, Frauke; Kräusslich, Hans-Georg; Konvalinka, Jan (Archives of biochemistry and biophysics, 2002)
Murine intracisternal A-type particles (IAPs) are endogenous retroviruses showing sequence homologies to B/D- and avian C-type retroviruses and a gene expression strategy similar to that of D-type retroviruses. These viruses form immature particles in the endoplasmic reticulum and do not release extracellular virions, but are competent for retrotransposition within the virus-producing cell. It had been assumed that lack of polyprotein processing and maturation is due to a defect in the viral proteinase (PR), but recent experiments have shown that polyprotein processing occurs when assembly of the mouse IAP MIA14 is artificially directed to the plasma membrane. We have expressed and purified recombinant MIA14 PR and show that it undergoes N- and C-terminal autoprocessing at defined sites. Using peptide cleavage and inhibition assays and in vitro cleavage of recombinant HIV-1 and MIA14 Gag polyproteins, we show that MIA14 PR is a catalytically competent enzyme comparable in its efficiency to PRs from type D exogenous retroviruses. MIA14 PR is related to the PR of Mason-Pfizer monkey virus both functionally and with respect to its expression strategy, and is distinct from HIV-1 PR with respect to substrate specificity and catalytic efficiency. These findings reveal a functional and possibly evolutionary relationship between MIA14 and D-type retroviruses and imply that a functional PR may be relevant for intracellular retrotransposition even in the case of an endogenous retrovirus that does not produce extracellular virus.
Keywords: Molecular Sequence Data; sekvence aminokyselin; Sequence Alignment; Open Reading Frames; geny pro IAP elementy; Retroviridae Proteins; aspartátové endopeptidasy; Mice; Endopeptidases; Aspartic Acid Endopeptidases; endopeptidasy; Cloning, Molecular; zvířata; Amino Acid Sequence; otevřené čtecí rámce; Retroviridae - proteiny; klonování DNA; myši; molekulární sekvence - údaje; sekvenční seřazení; Genes, Intracisternal A-Particle; Animals